Applications of evolutionary computation. 20th European Conference, EvoApplications 2017, Amsterdam, the Netherlands, April 19-21, 2017, Proceedings /: 20th European Conference, EvoApplications 2017, Amsterdam, the Netherlands, April 19-21, 2017, Proceedings. Part II : (2017) - Unknown
No abstract available